PENGEMBANGAN MEDIA KOTPEN (KOTAK PENGETAHUAN) BERBANTUAN AI PADA MUATAN IPAS KELAS IV DI SEKOLAH DASAR - Nabius, Riski; Abdullah, Gamar; Isnanto, Isnanto; Saleh, Meylan; Arif, R. Mardian (JURNAL PENDIDIKAN DASAR, 2024)
Abstract: This study aims to develop the KOTPEN (Knowledge Box) learning media assisted by AI for the Integrated Science and Social Studies (IPAS) subject in the 4th grade of elementary school. The research method used is a development research method with the ADDIE model. Based on validation results from experts and users, the Kotpen media received an average percentage score of 93.6% and was deemed highly suitable for use by teachers and students in elementary schools. In the practicality test of the Kotpen media, the researcher used a teacher observation sheet instrument, and the total score obtained was 38 out of a maximum score of 40, with an average score of 95%. Thus, the practicality percentage of using Kotpen media in learning reached 95%, which falls into the "very practical" category. In terms of the effectiveness of the Kotpen media, during its implementation in the 4th grade of SDN 18 Dungingi, teachers distributed pre-test and post-test questions to measure the media's effectiveness. The total pre-test score reached 36%, while the total post-test score reached 80%. The N-Gain calculation showed a score of 0.689, which falls into the "Moderate" category. Based on these results, it can be concluded that the Kotpen media is feasible, practical, and effective for use in elementary schools.Keywords: Learning Media, Kotpen (Knowledge Box), IPAS Abstrak: Penelitian ini bertujuan untuk mengembangkan media pembelajaran KOTPEN (Kotak Pengetahuan) berbantuan AI pada muatan IPAS kelas IV di Sekolah Dasar. Metode penelitian yang digunakan adalah metode penelitian pengembangan dengan menggunakan model ADDIE. Berdasarkan hasil validasi oleh para ahli dan pengguna, media Kotpen memperoleh hasil rekapitulasi nilai rata-rata persentase 93,6% dan dinyatakan sangat layak digunakan oleh guru dan siswa di SD. Dalam uji kepraktisan media kotpen, peneliti menggunakan instrumen lembar observasi guru dengan total skor yang diperoleh adalah 38 dari skor maksimum 40, dengan rata-rata skor 95%. Dengan demikian, persentase kepraktisan penggunaan media kotpen dalam pembelajaran mencapai 95%, yang termasuk dalam kategori sangat praktis. Dalam  keefektifan media kotpen, pada saat penerapan media di kelas IV SDN 18 Dungingi, guru membagikan soal pretest dan postets untuk mengukur keefektifan media. Total  nilai pretest mencapai 36%, sedangkan total nilai postest mencapai 80%. Perhitungan N-Gain menunjukkan nilai sebesar 0,689, yang masuk dalam kategori “Sedang”. Dengan hasil rekapitulasi ini maka dapat dinyatakan bahwa media kotpen layak, praktis dan efektif digunakan di SD.Kata Kunci: Media Pembelajaran, Kotpen (Kotak Pengetahuan), IPAS